2013
DOI: 10.1159/000354750
|View full text |Cite
|
Sign up to set email alerts
|

Skin Color Is Relevant to Vitamin D Synthesis

Abstract: Background: Whether dark skin produces less vitamin D after UVB radiation than fair skin remains controversial. Objective: To compare 25-hydroxyvitamin D [25-(OH)-D] levels after a single UVB exposure in fair (phototype II-III) and black-skinned (phototype VI) volunteers. Methods: Fair-skinned volunteers (n = 20, 4 males/16 females, mean age: 23.2 years) and black-skinned (n = 11, 6 males/5 females, mean age: 23.8 years) received a single total body UVB exposure (0.022 J/cm2). The 25-(OH)-D levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 21 publications
1
74
2
1
Order By: Relevance
“…In contrast, the concentration was <15 ng/mL in only 10-40% of the CKD patients in previous studies (9,(23)(24)(25)(26). One possible reason for this difference could be racial differences among the patient groups, since the main source of vitamin D is synthesis from the skin by sunlight, which differs among the races (2,27,28). Another reason could be the study period; the patients were enrolled in the winter season when 25(OH)D levels are usually lower due to shorter periods of sunlight (20,29).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the concentration was <15 ng/mL in only 10-40% of the CKD patients in previous studies (9,(23)(24)(25)(26). One possible reason for this difference could be racial differences among the patient groups, since the main source of vitamin D is synthesis from the skin by sunlight, which differs among the races (2,27,28). Another reason could be the study period; the patients were enrolled in the winter season when 25(OH)D levels are usually lower due to shorter periods of sunlight (20,29).…”
Section: Discussionmentioning
confidence: 88%
“…This finding may appear counterintuitive; however, detailed experimental studies of the relation between pigmentation and the response of 25(OH)D to UV radiation also found little correlation (30). Other observational epidemiologic studies showed no association between pigmentation and 25(OH)D concentrations (31), a negative correlation (32,33), and even a positive effect of skin pigmentation on serum concentratons of 25(OH)D (34). Further large studies will be required to answer this question.…”
Section: Discussionmentioning
confidence: 98%
“…One such factor is the amount of ultraviolet B rays emitted and absorbed, which are influenced by latitude and skin pigmentation, respectively [23]. In a study by Libon et al [24], serum vitamin D concentrations were evaluated in patients with light and dark skin pigmentation. Despite controlling for sun exposure, those with light skin pigmentation exhibited higher serum vitamin D concentrations compared to those with darker skin pigmentation.…”
Section: Metabolic and Physiological Aspects Of Vitamin Dmentioning
confidence: 99%